UNIT 1.28 Statistical Methods for Genome‐Wide and Sequencing Association Studies of Complex Traits in Related Samples. (20th January 2015) - Thornton, Timothy A.
Abstract : Genome‐wide association studies (GWAS) and sequencing studies are routinely conducted for the identification of genetic variants that are associated with complex traits. Many genetic studies for association mapping include related individuals. When relatives are included in an association analysis, familial correlations must be appropriately taken into account to ensure correct type I error and to increase power. This unit provides an overview of statistical methods that are available for GWAS and sequencing association studies of complex traits in samples with related individuals. © 2015 by John Wiley & Sons, Inc.